Dampak Kompetensi dan Komitmen Profesional Terhadap Kinerja Guru dengan Disiplin Kerja Sebagai Variabel Mediasi - Lutfiana, Fifi; Nurhayati, Mafizatun (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia (ADPEBI), 2025)
ABSTRACT The purpose of this study was to analyze the Influence of Teacher Competence and professional commitment on teacher performance with work discipline as an intervening variable. The method used in this study is a causal method with a quantitative approach. This study was conducted at SD Islam AL Ikhlas with a population of 87 employees and a sample used in this study of 80 teachers. The data collection technique used was a survey with a questionnaire instrument. Hypothesis testing in this study used structure equation modeling through Smart PLS software version 3.0. The results of this study indicate that teacher competence has a positive and significant influence on teacher performance. Teacher competence has a positive and significant influence on work discipline. Professional commitment has a positive and significant influence on teacher performance. Professional commitment has a positive and significant influence on work discipline. Furthermore, work discipline plays a partial mediating role in the influence of teacher competence on teacher performance, and work discipline plays a partial mediating role in the influence of professional commitment on teacher performance. Keywords: Teacher Competence, Professional Commitment, Teacher Performance, Work Discipline, SEM-PLS